1951
DOI: 10.2134/agronj1951.00021962004300100007x
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Temperature and Time of Day of Pollination to Seed Set in Oat Crossing1

Abstract: I N A PREVIOUS paper 3 it was pointed out that at Aberdeen, Idaho, oats flower most profusely in midafternoon. It was concluded that "The most favorable time of day for crossing oats at Aberdeen is between 2 and 5 o'clock in the afternoon, at which time blooming is at the maximum." Crossing operations performed at other times of the day usually were less successful. Also, the highest seed sets in oat crossing operations were obtained on days when maximum tempera-'Contribution from the Division of Cereal Crops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1954
1954
2015
2015

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Equipment consisted of scissors and straight pronged forceps. Except for a few variations, the technique was much the same as generally used by oat breeders, and explained by Coffman (3). Usually there were 2 or 3 days between emasculation and pollination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equipment consisted of scissors and straight pronged forceps. Except for a few variations, the technique was much the same as generally used by oat breeders, and explained by Coffman (3). Usually there were 2 or 3 days between emasculation and pollination.…”
Section: Methodsmentioning
confidence: 99%
“…Coffman ( 3) reported that natural anthesis of oats usually reached its maximum in the field between 3 and 4 p.m. at Arlington, Va., Aberdeen, Idaho, and Ames, Iowa. Hadden ( 5) observed that anthesis usually began at approximately 3:30 p.m. in South Carolina and lasted for about 1 hour.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Investigations by Riddell and Gries (1958) revealed Chinese Spring wheat matured early under cool-temperature short-day conditions, and was less sensitive to changes in photoperiod and temperature than White Federation 38 which was early in a long-day warm-temperature environment, ; Salmon (1914) found that temperatures of 30® to 40° C at flowering caused high sterility in wheat and concluded that the high incidence of floret sterility in the Great Plains during 1910-1912 was probably due to high temperature at heading. Coffman and Stevens (1951) noted that the highest seed set in oat crossing was obtained when maximum temperatures were 85° F or lower. When temperatures exceeded 95° F, successful crosses were few.…”
Section: Temperature and Morphological Developmentmentioning
confidence: 99%